Impact of Dialysis Adequacy on Patient Outcomes - Jules, Kabahizi (My University, 2006)
Introduction: Numerous studies have confirmed the association between the delivered dose of haemodialysis and patients outcomes. There is thus some evidence regarding the relationship between dialysis dose and quality of life. Objective: The study was designed to assess dialysis adequacy using urea kinetic modelling parameters and to determine the association between dialysis dose and patient outcomes. Methods: A retrospective review of the demographic and biochemical data of 61 patients on chronic haemodialysis in the year 2003 was performed and a prospective component was added to the study for quality of life and evaluation of cardiovascular comorbidity. Results: The mean delivered dose Kt/V was 1.34 ± 0.25. There was a statistically significant correlation (p<0.05) between dialysis dose and the following parameters: haemoglobin, physical dimension and its 3 scales, the SF-36 overall score, as well as between dialysis dose and sepsis. Conclusion: The dialysis dose correlated with a significant number of parameters including Hb and the physical components of the SF-36; hence, the importance of measuring the delivered dialysis dose of patient on maintenance dialysis in accordance with DOQI guidelines for improved patient outcomes is confirmed.
Faculty of Health Sciences, Degree of Master in Medicine. 9713161h
Keywords: dialysis; patient; studies; life; kinetic